2013
DOI: 10.3109/0284186x.2013.840739
|View full text |Cite
|
Sign up to set email alerts
|

No association found betweenCYP2D6genotype and early breast cancer events in tamoxifen-treated patients

Abstract: CYP2D6 genotype was not associated with tamoxifen treatment outcome, even when CYP2D6 inhibitor use, aromatase inhibitor use, or chemotherapy was taken into account. CYP2D6 genotype may be of minor importance for tamoxifen-treated patients in Scandinavia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The meta-analysis of the association between the variant/variant genotype (or inferred poor metabolizer phenotype) and breast cancer recurrence or mortality, as compared with the wild-type/wild-type genotype (or inferred extensive or ultrametabolizer phenotype), included 21 of the 31 studies. In 16 (76%) of these 21 studies, researchers extracted DNA from nonneoplastic tissue (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70), and in 5 of them (24%) they extracted DNA from tumor-infiltrated tissue (26-28, 46, 72). The summary estimates of association with and without bias analysis are reported in Table 3 and displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis of the association between the variant/variant genotype (or inferred poor metabolizer phenotype) and breast cancer recurrence or mortality, as compared with the wild-type/wild-type genotype (or inferred extensive or ultrametabolizer phenotype), included 21 of the 31 studies. In 16 (76%) of these 21 studies, researchers extracted DNA from nonneoplastic tissue (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70), and in 5 of them (24%) they extracted DNA from tumor-infiltrated tissue (26-28, 46, 72). The summary estimates of association with and without bias analysis are reported in Table 3 and displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, studies investigating the association between CYP2D6 genotype and clinical outcomes following treatment with tamoxifen for breast cancer have yielded conflicting evidence [69,[71][72][73][74]. Kiyotani et al [75] reported an important observation that in breast cancer patients who received tamoxifen therapy in combination with other therapies, there was no significant association between CYP2D6 genotype and recurrence-free survival.…”
Section: Genotype-dependent Susceptibility To Phenoconversionmentioning
confidence: 99%
“…Moreover, single nucleotide polymorphisms (SNPs) in the ESR1 gene, such as the intronic SNPs rs2234693 (PvuII; T > C) and rs9340799 (XbaI; A > G) [6], could influence the tumor response to the drug by a yet unexplored mechanism. Additionally, studies have addressed a genetic link in the metabolism of TAM and the risk of death from BC [7-23]. …”
Section: Introductionmentioning
confidence: 99%
“…TAM and its metabolites are further metabolized and inactivated by phase II enzymes, as SULT1A1 [17, 18]. Genetic variations within these drug-metabolizing enzymes affect TAM metabolism and effectiveness against ER-positive BC, and further pharmacogenomic studies are needed to clarify the available controversial data [1923]. …”
Section: Introductionmentioning
confidence: 99%